Precision Timing of Beta-Lactam Administration in Very Low Birth Weight Infants with Suspected Sepsis: A Multi-National Cohort Study - D Denge, Abhishek; Vanga, Yasaswi; Singh, Rashmi (Journal of Neonatal Surgery, 2025)
Background: Timely administration of antibiotics is critical in the management of sepsis, but evidence regarding optimal timing of beta-lactam administration in very low birth weight (VLBW) infants remains limited. This study investigated the association between precision timing of beta-lactam administration and clinical outcomes in VLBW infants with suspected sepsis. Methods: We conducted a retrospective multi-national cohort study across 4 neonatal intensive care units in 4 countries from January 2021 to December 2023. VLBW infants (birth weight <1500 g) with clinically suspected sepsis who received beta-lactam antibiotics were included. The primary outcome was all-cause 30-day mortality. Secondary outcomes included duration of mechanical ventilation, length of hospital stay, and development of antibiotic-resistant infections. Time-to-antibiotic was defined as the interval between clinical recognition of sepsis and administration of the first beta-lactam dose. Results: Among 58 VLBW infants with suspected sepsis (median gestational age 27.3 weeks [IQR 25.6-29.1], median birth weight 980 g [IQR 780-1250]), 14 (24.1%) had culture-confirmed sepsis. Median time-to-antibiotic was 65 minutes (IQR 42-95). Each hour delay in beta-lactam administration was associated with an increased risk of 30-day mortality (adjusted hazard ratio [aHR] 1.16, 95% CI 1.02-1.32, p=0.024), particularly in infants with culture-confirmed sepsis (aHR 1.28, 95% CI 1.05-1.55, p=0.012). Administration within 60 minutes was achieved in 46.6% (n=27) of cases and was associated with lower mortality compared to administration after 60 minutes (7.4% vs. 16.1%, p=0.042). Unit-level barriers to timely administration included delays in recognition, central line access difficulties, and medication preparation processes. Conclusions: Delayed beta-lactam administration in VLBW infants with suspected sepsis is associated with increased mortality, with each hour of delay conferring additional risk. Achieving administration within 60 minutes of sepsis recognition may improve outcomes in this vulnerable population. Quality improvement initiatives targeting identified barriers to timely antibiotic delivery are warranted.